2019
DOI: 10.3892/mmr.2019.10635
|View full text |Cite
|
Sign up to set email alerts
|

Piperine ameliorates the severity of fibrosis via inhibition of TGF‑β/SMAD signaling in a mouse model of chronic pancreatitis

Abstract: Chronic pancreatitis (CP) is characterized by recurrent pancreatic injury, resulting in inflammation and fibrosis. Currently, there are no drugs for the treatment of pancreatic fibrosis associated with CP. Piperine, a natural alkaloid found in black pepper, has been reported to show anti-inflammatory, anti-oxidative, and antitumor activities. Although piperine exhibits numerous properties in regards to the regulation of diverse diseases, the effects of piperine on CP have not been established. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The EMT process is characterized by morphological, phenotypic and biochemical alterations, which together influence the behavior of tumor cells of epithelial origin [74]. In the literature, many studies have shown that piperine modulates crucial events related to EMT process, such as cell motility [22], MMP expression and activity [30], expression of mesenchymal proteins [18], as well as the activation of MAPK and SMAD signaling pathways [18,75]. However, so far, no study has demonstrated the ability of piperine to collectively compromise all of these events in cancer cells undergoing EMT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The EMT process is characterized by morphological, phenotypic and biochemical alterations, which together influence the behavior of tumor cells of epithelial origin [74]. In the literature, many studies have shown that piperine modulates crucial events related to EMT process, such as cell motility [22], MMP expression and activity [30], expression of mesenchymal proteins [18], as well as the activation of MAPK and SMAD signaling pathways [18,75]. However, so far, no study has demonstrated the ability of piperine to collectively compromise all of these events in cancer cells undergoing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Choi et al [18] demonstrated that in a murine study of chronic pancreatitis, piperine attenuated the production of TGF-β in the pancreas and improved the severity of fibrosis through inhibition of TGF-β/SMAD signaling pathways. The authors also demonstrated that in TGFβ-treated pancreatic stellate cells, piperine reduced the expression of the mesenchyml markers αSMA, FN and collagen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations